Revised Kuppuswamy and B G Prasad socio-economic scales for 2016 - Shaikh, Zakirhusain; Pathak, Rambha (International Journal Of Community Medicine And Public Health, 2017)
Background: Socio-economic scales are integral part in the assessment of social class of an individual/family, which can have an influence on disease causing factors. It is also vital for consideration when customising health education to the target audience. Socio-economic scales are dependent on evaluation of income and need to be updated with changing consumer price index. The objective of the study was to revise the socio-economic scales of Kuppuswamy and B G Prasad, taking into consideration the revision in consumer price index (industrial workers). Methods: The socio-economic scales were revised on the basis of updated CPI (IW) for the month of August 2016, using an online tool. Results: The updated Kuppuswamy and B G Prasad scales for the year 2016 were obtained using revised CPI (IW) and a simple online tool. Conclusions: Regular updating of socio-economic scales which depend on income and are therefore susceptible to changes, due to revisions in consumer price index, is necessary to maintain the validity of these scales, which are used widely in community surveys and social studies.